To develop the equation representing the total cost \( C \) of being a member for \( m \) months, we need to consider both the one-time startup fee and the monthly maintenance cost.
Let’s assume:
- The one-time startup fee is \( S \).
- The monthly cost is \( P \).
The equation for the total cost can be expressed as:
\[ C = S + P \cdot m \]
Now, if we fill out the table for \( m = 0, 1, 2, 3, 4, 5 \), we need the specific values for \( S \) and \( P \) to provide a numerical solution. However, I can demonstrate how to fill out the table with placeholders.
Assume:
- Startup fee \( S = 100 \) (for example)
- Monthly cost \( P = 20 \) (for example)
Using these values, the equation becomes:
\[ C = 100 + 20m \]
Now, let’s fill out the table:
| Months (\( m \)) | Total Cost (\( C \)) | |-------------------|----------------------| | 0 | \( 100 + 20 \times 0 = 100 \) | | 1 | \( 100 + 20 \times 1 = 120 \) | | 2 | \( 100 + 20 \times 2 = 140 \) | | 3 | \( 100 + 20 \times 3 = 160 \) | | 4 | \( 100 + 20 \times 4 = 180 \) | | 5 | \( 100 + 20 \times 5 = 200 \) |
Thus, the completed table with this specific example would look like:
| Months (\( m \)) | Total Cost (\( C \)) | |-------------------|----------------------| | 0 | 100 | | 1 | 120 | | 2 | 140 | | 3 | 160 | | 4 | 180 | | 5 | 200 |
Feel free to replace \( S \) and \( P \) with the actual values to get specific total costs.